2009
DOI: 10.1124/jpet.108.146522
|View full text |Cite
|
Sign up to set email alerts
|

Colchicine: A Novel Positive Allosteric Modulator of the Human 5-Hydroxytryptamine3AReceptor

Abstract: The actions of colchicine were examined with the two-electrode voltage-clamp technique and radioligand binding assays in mouse and human 5-hydroxytryptamine 3A receptors (5-HT 3A Rs) expressed in Xenopus laevis oocytes. Colchicine inhibited 5-hydroxytryptamine (5-HT)-evoked currents in oocytes expressing mouse 5-HT 3A Rs, with an IC 50 of 59.5 Ϯ 3 M. In contrast to the mouse receptor, coapplication of colchicine with 5-HT (Ͻ1 M) strongly enhanced 5-HT-evoked currents in oocytes expressing human 5-HT 3A Rs. Col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Colchicine can affect other ligand‐gated ion channels acutely, such as the GABA A and 5‐HT 3 receptors, either negatively or positively (Weiner et al ., 1998; de Oliveira‐Pierce et al ., 2009). All the previous experiments were performed under the assumption that the microtubule depolymerizing property of colchicine was important for its effect on permeabilization, and therefore, a 1 h pre‐incubation with this agent was justifiable.…”
Section: Resultsmentioning
confidence: 99%
“…Colchicine can affect other ligand‐gated ion channels acutely, such as the GABA A and 5‐HT 3 receptors, either negatively or positively (Weiner et al ., 1998; de Oliveira‐Pierce et al ., 2009). All the previous experiments were performed under the assumption that the microtubule depolymerizing property of colchicine was important for its effect on permeabilization, and therefore, a 1 h pre‐incubation with this agent was justifiable.…”
Section: Resultsmentioning
confidence: 99%
“…This suggestion can be supported by earlier reports which showed that stimulated radioligand binding caused by positive allosteric modulator was typical. 30 , 31 Additional studies would be worthwhile to evaluate the effect of RAF of Abs to S100 on radioligands affinity to the corresponding receptors in binding saturation assays as well as assays that evaluate receptor function under conditions appropriate for allosteric receptor modulation.…”
Section: Discussionmentioning
confidence: 99%
“…X. laevis oocyte membranes expressing mouse wild-type 5-HT 3A Rs were isolated by homogenization and centrifugation as described elsewhere (de Oliveira-Pierce et al, 2009). Briefly, ~100 oocytes were homogenized in ice-cold VDB (100 μL/oocyte) in the presence of protease inhibitor cocktail III (2 μL/mL) using a motorized glass potter.…”
Section: Methodsmentioning
confidence: 99%